1995
DOI: 10.1074/jbc.270.48.28989
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Pyruvate Dehydrogenase Kinase Gene Family in Humans

Abstract: ) J. Biol. Chem. 269, 29720 -29724). The present study was undertaken to further explore the diversity of the pyruvate dehydrogenase kinase gene family. Here we report the deduced amino acid sequences of three isoenzymic forms of PDK found in humans. In terms of their primary structures, two isoenzymes identified in humans correspond to rat PDK1 and PDK2, whereas a third gene (PDK3) encodes for a new isoenzyme that shares 68% and 67% of amino acid identities with PDK1 and PDK2, respectively. PDK3 cDNA expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
200
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(205 citation statements)
references
References 25 publications
3
200
0
2
Order By: Relevance
“…To date, four isoforms of PDK isoenzymes (PDKs) have been identified in mammals [5,6]. PDKs are mitochondria genes and belong to histidine kinase-like ATPases family.…”
Section: Introductionmentioning
confidence: 99%
“…To date, four isoforms of PDK isoenzymes (PDKs) have been identified in mammals [5,6]. PDKs are mitochondria genes and belong to histidine kinase-like ATPases family.…”
Section: Introductionmentioning
confidence: 99%
“…Expression Vector Construction-The cloning vectors harboring the human PDK2 and PDK3 cDNA inserts were a kind gift from Kirill M. Popov and Robert A. Harris (6). For PDK2, PCR was performed with Pfu DNA polymerase (Stratagene) using primers that produced a 1.2-kilobase pair product encoding mature PDK2 with a 5Ј NheI site and a 3Ј HindIII site introduced.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, because the nematode trPDKs still seem to be dimers, as judged by chromatography on Superose 12, this C-terminal domain does not seem to be involved in subunit association. A number of conserved domains were identified when the sequences of PDKs from different sources were compared [7]. Interestingly, sequence conservation is present in the C-terminal binding region among all these PDKs (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mammalian PDK isoforms have been identified that seem to have unique tissue distributions and physiological roles [5][6][7][8][9]. Interestingly, although these PDK isoforms phosphorylate serine residues, they lack motifs usually present in eukaryotic Ser\Thr kinases and exhibit significant sequence identity with histidine protein kinases best characterized in prokaryotic signal transduction [6,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation